2017
DOI: 10.1002/ana.25095
|View full text |Cite
|
Sign up to set email alerts
|

A localized pallidal physiomarker in cervical dystonia

Abstract: Our findings suggest that theta oscillations in the internal pallidum are robustly associated with dystonic symptoms in cervical dystonia and may be a useful biomarker for adaptive closed-loop stimulation. Furthermore, theta oscillatory activity may have a predictive value for the clinical benefit after chronic DBS that could be used to improve intraoperative neurophysiological target mapping during electrode implantation. Ann Neurol 2017;82:912-924.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
123
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 51 publications
13
123
2
Order By: Relevance
“…However, more recent evidence has suggested that indeed most STN neurons increase, rather than decrease, spiking activity during movement (Nambu et al, 2002; Goldberg et al, 2013; Zavala et al, 2017a). Furthermore, increased STN theta activity has been implicated in pathologies that involve excess movement such as dystonia, dyskinesia, impulsivity, and OCD (Alonso-Frech et al, 2006; Rodriguez-Oroz et al, 2011; Neumann et al, 2012, 2017; Rappel et al, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…However, more recent evidence has suggested that indeed most STN neurons increase, rather than decrease, spiking activity during movement (Nambu et al, 2002; Goldberg et al, 2013; Zavala et al, 2017a). Furthermore, increased STN theta activity has been implicated in pathologies that involve excess movement such as dystonia, dyskinesia, impulsivity, and OCD (Alonso-Frech et al, 2006; Rodriguez-Oroz et al, 2011; Neumann et al, 2012, 2017; Rappel et al, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…Overall, 3 to 12 Hz peaks occurred in 168 of 240 analyzed individual recordings. Beta peaks (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) could be detected in every patient, but not at all timepoints (range 2-16 of 30 recordings per patient), adding up to a total of 94 of 240 analyzed recordings, with overall lower amplitude. No other distinct peaks were revealed in higher frequency bands.…”
Section: Resultsmentioning
confidence: 95%
“…This correlation was frequency specific to low frequency, but not beta band, and replicates previous work reporting an association between pallidal low-frequency power and motor sign severity in patients with cervical dystonia. 15 In Parkinson's disease, beta activity in the basal ganglia has been shown to: 1) be reduced by dopaminergic medication and DBS, 2) correlate with motor sign severity and 3) be preserved after long-term stimulation. 20,27 Because of this modulation and stability over time, recent studies used beta activity as a feedback signal for demand-dependent, adaptive closed-loop stimulation and have already achieved promising preliminary results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations